Protective effects of an Fc-engineered PD-L1 fusion protein in a spontaneous abortion model and a Th17 cell–induced pregnancy loss model - Li, Guangyao; Wang, Tiantian; Tan, Dan; Jin, Yamin; Zhou, Xuemei; Ai, Hongru; Zheng, Xinya; Ren, Xiaochen; Hu, Shi; Lei, Changhai; Fu, Wenyan (Frontiers in Pharmacology, 2025)
The binding of programmed death-ligand 1 (PD-L1) with its receptor PD-1 has been proven to negatively regulate immune responses. Here, we assessed the therapeutic effects of Fc-fused PD-L1 protein on foetomaternal tolerance using a murine spontaneous abortion model and a Th17 cell-induced abortion model. Fc-engineered recombinant PD-L1-Fc showed negligible cytotoxicity to PD1-positive cells. The abortion rates in the CBA/J × DBA/2 mouse model were significantly ameliorated after PD-L1-Fc treatment. Additionally, PD-L1-Fc administration decreased the expression of interleukin (IL)-17A and diminished the frequency of IL-17A-producing CD4+ T cells in the decidua of treated mice. The foetomaternal protective effect of PD-L1-Fc was also observed in a Th17 cell transfer-induced abortion mouse model. These results indicate that PD-L1-Fc may provide a novel therapeutic strategy to treat spontaneous abortion involving immune factors.